Stories, Traces of Discourse, and the Tease of Presence: Gertrude Simmons Bonnin as Orator and Indigenous Activist - (:unkn) unknown (My University, 2013)
An accomplished writer, editor, musician, teacher, organizer, lobbyist, and political reformer, Gertrude Simmons Bonnin worked tirelessly during the first half of the twentieth century to enhance opportunities for Native Americans. Literary texts authored by Bonnin (writing as Zitkala-Sa) are well known, but her legacy as an early twentieth-century orator and indigenous activist receives little critical attention. Emerging histories within rhetoric and composition continue to recover generally ignored or previously marginalized voices, but we still lack studies specifically examining public speeches made by individuals, particularly women, who sought to both survive within dominant American society, and simultaneously maintain, if not advance, sovereign forms of identity, community, and culture. A careful review of Bonnin's early twentieth-century efforts to advance indigenous concerns provides scholars with rich opportunities to examine rhetoric from perspectives beyond the Western Eurocentric canon. Her rhetorical maneuvers as an orator, particularly between 1920 and 1925, frequently invoked Dakota culture and continually reworked Western Eurocentric rhetorical forms--specifically epideixis and ethos--as sites of agency and resistance. Recovering this history enriches our understanding of survivance as articulated by Gerald Vizenor and continues to enlarge our understanding of multivalent, cross-cultural forms of rhetorical production. This project recovers and critically analyzes an important legacy of early twentieth-century political activism, illustrating powerful means for effectively resisting, essentially refiguring, and meaningfully confronting prevailing discourses of erasure, inequality, or exclusion. The rhetorical strategies Gertrude Simmons Bonnin devised and employed as a public figure are worthy of scholarly attention, most notably for their ability to create discursive formations which affirm and sustain indigeneity from both within, and beyond, dominant culture.
Keywords: Epideictic; Epideixis; Ethos; Feminist Rhetorical History; Survivance